2015
DOI: 10.1037/adb0000003
|View full text |Cite
|
Sign up to set email alerts
|

An examination of college student activities and attentiveness during a web-delivered personalized normative feedback intervention.

Abstract: Both heavy drinking and related risky sexual behavior among college students are common and are often associated with a number of negative consequences. A previously reported randomized controlled trial showed that a brief personalized normative feedback (PNF) intervention reduced the alcohol consumption and alcohol-related risky sexual behavior of heavy drinking, sexually active college students (Lewis et al., in press). For the present study, we examined what activities students were engaged in when viewing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…There is some evidence that computer-delivered interventions administered in-person to non-treatment-seeking heavy drinking students work relatively well, whereas computer-delivered interventions that are administered remotely may not work at all for the same population (Rodriguez et al, 2015). This is consistent with research showing that students participating in remotely-delivered web-based intervention studies are frequently engaged in multiple activities at the same time (e.g., watching television, checking email, talking or texting on phones; Lewis & Neighbors, 2015). The same study also demonstrated that the intervention effect in drinking reductions was only evident among participants who reported being attentive or not preoccupied while attending to the intervention.…”
Section: Discussionsupporting
confidence: 88%
“…There is some evidence that computer-delivered interventions administered in-person to non-treatment-seeking heavy drinking students work relatively well, whereas computer-delivered interventions that are administered remotely may not work at all for the same population (Rodriguez et al, 2015). This is consistent with research showing that students participating in remotely-delivered web-based intervention studies are frequently engaged in multiple activities at the same time (e.g., watching television, checking email, talking or texting on phones; Lewis & Neighbors, 2015). The same study also demonstrated that the intervention effect in drinking reductions was only evident among participants who reported being attentive or not preoccupied while attending to the intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Across delivery modalities, five trials that did not alter norm perceptions did not provide gender-specific feedback (LaChance et al, 2009; Larimer et al, 2007; Martens et al, 2010; Neighbors et al, 2010, Condition 4; Pedersen, 2012). Thus, it may prove more difficult to change descriptive norms (a) when interventions are delivered remotely to students who may be distracted (Lewis & Neighbors, 2014; Rodriguez et al, 2015); (b) when national rather than local norms serve as the basis for normative feedback; and (c) when gender non-specific normative feedback is utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Among the internet and mailed trials that did not find evidence of mediation, six of seven internet and two of three mailed trials had at least one mediator that was not affected by the intervention (no a paths). Psychosocial constructs may be more difficult to change when content is delivered remotely because students are often distracted by other activities (Lewis & Neighbors, 2014), preventing the deep processing required for effecting change (Petty & Cacioppo, 1986). Altering mediators does not require delivering content via counselor, as evidenced by the computer-delivered trials.…”
Section: Resultsmentioning
confidence: 99%
“…The survey was modeled on standard web-based PNF (Lewis & Neighbors, 2015; Neighbors et al, 2004). Participants answered questions about their perceptions of the drinking behaviors of the typical student of their same sex and class year and then reported their own alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have, therefore, speculated that doubts about the credibility of drinking statistics presented (LaBrie, Hummer, Neighbors, & Larimer, 2010; Hummer & Davison, 2016), defensive reactions among heavy drinkers (Granfield, 2005; Steers, Coffman, Wickham, Bryan, Caraway, et al, 2016), and general inattention to feedback (Lewis & Neighbors, 2015) may be responsible for the modest effects observed. Surprisingly, although approximately 100 published studies during the past two decades have evaluated PNF components (Larimer & Cronce, 2002; Cronce & Larimer, 2011; Dotson et al, 2015); innovation seeking to rectify these limitations has been slow to emerge.…”
Section: Introductionmentioning
confidence: 99%